2020
DOI: 10.1007/s40722-020-00173-9
|View full text |Cite
|
Sign up to set email alerts
|

Beyond VoF: alternative OpenFOAM solvers for numerical wave tanks

Abstract: The vast majority of numerical wave tank applications are solved using finite volume-based, volume of fluid methods. One popular numerical modelling framework is OpenFOAM and its two phase solvers, interFoam and interIsoFoam, enabling the simulation of a broad range of marine hydrodynamic phenomena. However, in many applications, certain aspects of the entire set of possible hydrodynamic phenomena are not of interest and the reduced complexity could allow the use of simpler, more computationally efficient solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Schmitt et al [22] explored the choice of solvers in OpenFOAM other than those based on the VOF method, which could be utilised to implement numerical wave tanks, namely: potentialFreeSurfaceFoam and shallowWaterFoam. While hundreds of publications have utilised the VOF method for WSI, Schmitt et al [22] found that less than a dozen have used shallowWaterFoam and only two have used potentialFreeSurfaceFoam.…”
Section: Alternative Methodsmentioning
confidence: 99%
“…Schmitt et al [22] explored the choice of solvers in OpenFOAM other than those based on the VOF method, which could be utilised to implement numerical wave tanks, namely: potentialFreeSurfaceFoam and shallowWaterFoam. While hundreds of publications have utilised the VOF method for WSI, Schmitt et al [22] found that less than a dozen have used shallowWaterFoam and only two have used potentialFreeSurfaceFoam.…”
Section: Alternative Methodsmentioning
confidence: 99%
“…The phase fraction on each cell face, i.e. the interpolated value, is then calculated [22] from the amount submerged below the surface cut. MPLIC is for handling multiple surface cuts, where a single cut in one cell is insufficient, e.g.…”
Section: Wave Flowmentioning
confidence: 99%
“…Alternative methods. Schmitt et al [22] explored the choice of solvers in OpenFOAM other than those based on the VOF method, which could be utilised to implement numerical wave tanks, namely: potentialFreeSurfaceFoam and shallowWaterFoam. While hundreds of publications have utilised the VOF method for WSI, Schmitt et al [22] found that less than a dozen have used shallowWaterFoam and only two have used potentialFreeSurfaceFoam.…”
Section: Wave Flowmentioning
confidence: 99%
See 2 more Smart Citations